Pengaruh DAR, WCTO, NPM, Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan Food And Beverage - Sinthia Anggi Sitepu; Meriana Situmorang; Mei Linda Siregar; Marice Habeahan; Jelita Bakara (Universitas Muhammadiyah Sorong, 2019)
The size of the company's value can be measured through stock prices. The higher the stock price, the higher the profit gained by the company. This study aims to examine the effect of debt to asset ratio, working capital turnover, net profit margin, and Sales Growth on company value on Food and Beverage companies listed on the Indonesia Stock Exchange in 2012-2017. The analysis model used is multiple regression. The population of this study was 21 companies with a sample of 12 companies. This sampling technique uses purposive sumpling. The results of this study indicate simultaneously debt to asset ratio, working capital turnover, net profit margin, and Sales Growth have no significant effect on firm value. While partially debt to asset ratio has no significant effect, working capital turnover partially has no significant effect, net profit margin partially has a significant effect and Sales Growth partially has no significant effect.